Transesterification of sunflower oil catalyzed by flyash-based solid catalysts - Kotwal, M. S.; Niphadkar, P. S.; Deshpande, Suvarna S.; Bokade, Vijay V.; Joshi, P. N. (Fuel, 2009)
Flyash-based base catalyst was used in the transesterification of sunflower oil with methanol to methyl esters in a heterogeneous manner. Catalyst preparation variables such as, the KNO(3) loading amount and calcination temperature were optimized. The catalysts were characterized by powder XRD. The catalyst prepared by loading of 5 wt.% KNO(3) on flyash followed by its calcination at 773 K has exhibited maximum oil conversion (87.5 wt.%). The influence of various reaction parameters such as % catalyst loading, methanol to oil molar ratio, reaction time, temperature, reusability of the catalyst on the catalytic activity was investigated. K(2)O derived from KNO(3) might be an essential component in the catalyst for its efficiency. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Flyash; heterogeneous catalyst; Methyl ester; Sunflower oil; transesterification

Thermal expansion properties of stannosilicate molecular sieve with MFI type structure - Niphadkar, P. S.; Bhange, Deu S.; Selvaraj, K.; Joshi, P. N. (Chemical Physics Letters, 2012)
An in situ high temperature X-ray diffraction study was carried out for investigating the thermal expansion properties of Si-MFI and SnSi-MFI molecular sieves. The thermal stability up to 973 K and a negative lattice thermal expansion in anisotropic manner was exhibited by both the phases in the temperature range of 373-973 K. The trend observed in contraction along the axes was as: a > c > b. The substitution of Sn4+ in MFI framework resulted in an expansion of unit cell volume and in an increase in the lattice thermal expansion coefficient in the temperature range 423-973 K. (C) 2012 Elsevier B. V. All rights reserved.